2011
DOI: 10.1007/s11011-010-9230-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential distribution of heparan sulfate glycoforms and elevated expression of heparan sulfate biosynthetic enzyme genes in the brain of mucopolysaccharidosis IIIB mice

Abstract: The primary pathology in mucopolysaccharidosis (MPS) IIIB is lysosomal storage of heparan sulfate (HS) glycosaminoglycans, leading to complex neuropathology and dysfunction, for which the detailed mechanisms remain unclear. Using antibodies that recognize specific HS glycoforms, we demonstrate differential cell-specific and domain-specific lysosomal HS-GAG distribution in MPS IIIB mouse brain. We also describe a novel neuron-specific brain HS epitope with broad, non-specific increase in the expression in all n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 53 publications
1
10
0
Order By: Relevance
“…In MPSs, the lysosomal accumulation of undigested GAGs is considered the "primum movens" of the subsequent functional cell impairment; however, evidence demonstrates that the accumulation of storage material does not occur only in the lysosomes, but also on the cell surface and ECM where GAGs form proteoglycans through their covalent binding to a core protein [105,106,109]. The accumulation of storage material in non-lysosomal compartments accounts for impaired cell signaling and trafficking, protein unfolding, abnormal autophagy, alterations of intracellular calcium homeostasis, lysolipid accumulation, and modifications in other cellular processes that ultimately lead to the MPS phenotypes [150][151][152][153][154][155][156][157][158][159].…”
Section: Cathepsin Involvement In the Pathophysiology Of Mucopolysaccmentioning
confidence: 99%
“…In MPSs, the lysosomal accumulation of undigested GAGs is considered the "primum movens" of the subsequent functional cell impairment; however, evidence demonstrates that the accumulation of storage material does not occur only in the lysosomes, but also on the cell surface and ECM where GAGs form proteoglycans through their covalent binding to a core protein [105,106,109]. The accumulation of storage material in non-lysosomal compartments accounts for impaired cell signaling and trafficking, protein unfolding, abnormal autophagy, alterations of intracellular calcium homeostasis, lysolipid accumulation, and modifications in other cellular processes that ultimately lead to the MPS phenotypes [150][151][152][153][154][155][156][157][158][159].…”
Section: Cathepsin Involvement In the Pathophysiology Of Mucopolysaccmentioning
confidence: 99%
“…1,3 While detailed mechanisms of pathology, especially the neuropathology of MPS III, are not yet well understood, numerous studies have reported cascades of complex secondary pathological events in the CNS, including broad metabolic impairments, [4][5][6] neuroinflammation, 5,7-11 oxidative stress, 10,12 autophagy, 13,14 and neurodegeneration. 7,9,11,[15][16][17][18][19][20] It is worth noting that many of these secondary neuropathological features of MPS IIIB, such as b-amyloid (Ab) aggregation, 15,18 tauopathy, 17,18 synucleinopathy, 16,19 oxidative stress, 10,12 and neuroimflammation, 5,[7][8][9][10][11] are also common hallmarks of other neurodegenerative diseases like Alzheimer's (AD) 21,22 and Parkinson's disease (PD). 23,24 In addition, our recent studies demonstrate widespread profound neuropathology in the peripheral nervous system (PNS), 25 indicating that neuropathological manifestation affects the entire nervous system.…”
Section: Mucopolysaccharidosis (Mps) Iiib (Online Mendelian Inheritanmentioning
confidence: 99%
“…Further, it is commonly accepted that in the brain, multiple factors contribute to the neuropathology, secondary to the primary pathology- the lysosomal storage of HS-GAGs [4], [6], [7], [8], [9], [10], [11], [12], [13], [14]. The complex MPS IIIB neuropathology has been shown to involve impaired metabolism, inflammation, neurodegeneration, reactive oxygen species and tauopathy.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the lysosomal storage pathology of MPS IIIB is global throughout the CNS and neuropathology studies have focused predominantly on changes in the brain, though previous studies showed lysosomal storage lesions in all parts of the CNS in mice and dogs [4] , [5] . Further, it is commonly accepted that in the brain, multiple factors contribute to the neuropathology, secondary to the primary pathology- the lysosomal storage of HS-GAGs [4] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] . The complex MPS IIIB neuropathology has been shown to involve impaired metabolism, inflammation, neurodegeneration, reactive oxygen species and tauopathy.…”
Section: Introductionmentioning
confidence: 99%